The Effect of the Use of Quipper School-Based Indonesian History E-Learning Learning Media on the Interest and Learning Outcomes of Class X Students of SMK N 04 Kendal - Ratri, Sifi Dianing; Bain, Bain; Amin, Syaiful (Universitas Negeri Semarang, 2020)
The purpose of this research was 1) to know the interest and learning outcome of the tenth graders at SMK N 04 Kendal before using e-learning quipper-based history learning media, 2) to know the difference in student interest and learning outcomes that use and who do not use e-learning media based on quipper school 3) to know the effect of using e-learning quipper school-based as history learning media towards the interest and learning outcome of the tenth graders at SMK N 04 Kendal. This research was experimental, using a quasi-experimental design with a nonquivalent control group design and survey method. The results of this research show that there is before using e-learning media based on Quipper's interest in learning, the average score of students' learning interest in the class was 67.83 with sufficient category and student learning outcomes before using e-learning media based on Quipper school is still under KKM (Minimal Mastery Criteria) 25.97 for pretest control class and 37.36 for pretest experiment class. The results t-test of students' learning interest shows a t value count as much as 9.084> 1.994 (t table), and the results t-test of students' learning outcomes shows t value count as much as 6.587 > 1.994 (t table). Therefore, there is a difference in interest and learning outcomes in the classroom that use and who do not use e-learning media based on Quipper school—using e-learning Quipper school-based history learning media towards students’ interest 40,3% and students’ learning outcomes as much as 27,5%. Therefore, the use of e-learning quipper school-based history learning media influences the interest and learning outcomes of the tenth graders at SMK N 04 Kendal.